ANALISIS PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA PENGINAPAN KURNIA PASIR PENGARAIAN - SYAHPUTRA, ANGGI (Jurnal Mahasiswa Prodi Manajemen Fakultas Ekonomi, 2015)
This research aimed to analyze the level of customer satisfaction stayingin Penginapan Kurnia with the quality of services provided. The samplingtechnique is purposive sampling sampling techniques with special considerationthat deserves to be sampled. The results showed that the TCR values forindicators of physical evidence, reliability, assurance, responsiveness, andempathy in fairly good condition, while customer satisfaction in good condition.Quality of service significantly influence customer satisfaction. Her advice thatshould Penginapan Kurnia improve service quality dimensions in order to providean optimal guest satisfaction.